The IMPACT OF 12% TAX INCREASE ON UNEMPLOYMENT RATE AND ECONOMIC GROWTH: A MACROECONOMIC ANALYSIS OF INDONESIA - Maulidya, Rahmanita; Asriati, Nuraini (LP2M Universitas Perjuangan Tasikmalaya, 2024)
The 12% increase in the Value Added Tax (VAT) rate in Indonesia raises concerns about its impact on the unemployment rate and economic growth. This article analyzes the implications of this fiscal policy using a macroeconomic approach and systematic literature review method. The process of coding and visualizing the research results uses Atlas.ti software. The findings suggest that the tax increase has the potential to burden firms, which could lead to a reduction in labor force and increase unemployment, especially in sectors that depend on people's purchasing power. In this situation, higher inflation could erode purchasing power, reduce demand for goods and services, and slow overall economic growth. This research suggests that an increase in unemployment will have a wider negative impact on the economy, as the informal sector tends to be more vulnerable to these fluctuations. Keywords: Value Added Tax (VAT), Increase in VAT rate, Unemployment, Economic growth, Macroeconomic approach.